Beispiel Nr: 07
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(-1/0)\qquad Q(4/0) \\\\ \\ \textbf{Rechnung:} \\ P(-1/0)\qquad Q(4/0) \qquad a=-7 \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=-7(x+1)(x-4)\\ y=-7(x^2+x \cdot 1 +\left(-4\right)\cdot x +1\cdot \left(-4\right) )\\ y=-7(x^2 -3 x-4) \\ y= -7x^2+21x+28 $